2017
DOI: 10.1016/bs.mie.2017.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Chemoenzymatic Synthesis and Applications of Prokaryote-Specific UDP-Sugars

Abstract: This method describes the chemoenzymatic synthesis of several nucleotide sugars, which are essential substrates in the biosynthesis of prokaryotic N- and O-linked glycoproteins. Protein glycosylation is now known to be widespread in prokaryotes and proceeds via sequential action of several enzymes, utilizing both common and modified prokaryote-specific sugar nucleotides. The latter, which include UDP-hexoses such as UDP-diNAc-bacillosamine (UDP-diNAcBac), UDP-diNAcAlt, and UDP-2,3-diNAcManA, are also important… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…Nevertheless, AcCoA is too expensive to do large‐scale synthesis. Chemical acetylation has been proven to produce acetylated sugar nucleotides in multimilligram‐scale, [44] but it needs the separation of amino sugar in pure form. Therefore, we turn to do the enzymatic acetylation by employing a AcCoA regeneration system.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, AcCoA is too expensive to do large‐scale synthesis. Chemical acetylation has been proven to produce acetylated sugar nucleotides in multimilligram‐scale, [44] but it needs the separation of amino sugar in pure form. Therefore, we turn to do the enzymatic acetylation by employing a AcCoA regeneration system.…”
Section: Resultsmentioning
confidence: 99%
“…The subsequent amination of UDP‐4‐keto‐6‐deoxy‐GlcNAc or UDP‐4‐keto‐6‐ deoxy‐Glc at the C‐4 position by transaminase resulted in UDP‐ D‐4n‐FucNAc or UDP‐D‐4n‐QuiNAc [43] . However, it is difficult to obtain pure UDP‐D‐4n‐FucNAc or UDP‐D‐4n‐QuiNAc in sufficient quantity by enzymatic synthesis [43, 44] . The amino donor of transaminase is PMP, which is regenerated from pyridoxal‐5′‐phosphate (PLP) and L‐Glutamate without the need of an exogenous enzyme (Figure 1, CRS4).…”
Section: Resultsmentioning
confidence: 99%
“…UDP-linked amino sugars are difficult to synthesize, however, chemical, enzymatic and chemoenzymatic approaches have been explored ( Koizumi et al, 1998 ; Ahmadipour and Miller 2017 ; Zamora et al, 2017 ; Ahmadipour et al, 2018 ; Ahmadipour et al, 2019 ; Mikkola, 2020 ). Chemical synthesis of activated carbohydrates is demanding and relies on specialized expertise in carbohydrate chemistry; however, due to the lack of alternative routes, it remains a popular choice to synthesize non-natural sugar nucleotides (e.g., fluorinated nucleotide sugars) ( Wagner et al, 2009 ; Tedaldi et al, 2012 ), which may serve for the synthesis of modified oligosaccharides, as enzyme inhibitors and/or in diagnostics ( Mikkola, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, chemical approaches also suffer from other major drawbacks such as lack of stereoselectivity, tedious purification processes, and a low space-time yield ( Zhao et al, 2010 ). Chemoenzymatic syntheses use biotransformation steps together with simple chemical steps, thus improving efficiency and enabling the synthesis of chemically defined nucleotide-activated sugars ( Zamora et al, 2017 ). Using glucosamine and ATP as substrates and hexokinase, GlmM, and GlmU, Heidlas et al (1992) firstly showed the enzymatic synthesis of UDP-GlcNAc.…”
Section: Discussionmentioning
confidence: 99%
“…21 Cristina Zamora (MIT, USA) closed the session by describing her studies of Campylobacter jejuni pathogenicity, one of the main causes of gastroenteritis. 22 Using an innovative human intestinal immune-competent microphysiological system, Zamora explored the role of N-glycans in C. jejuni infection via the Pgl pathway. She uncovered the multifaceted importance of the Pgl pathway in C. jejuni host−pathogen interactions and characterized the importance of chemokine and cytokines profiles and the different composition of virulence-associated outer-membrane vesicles in pathogenesis.…”
mentioning
confidence: 99%